RETRACTED: Touchless palm print recognition system design using Gray Level Co-occurrence Matrix feature with K-Nearest Neighbor classification in MATLAB - Rochendi, Agus Dendi; Silalahi, Lukman Medriavin; Simanjuntak, Imelda Uli Vistalina (Universitas Mercu Buana, 2024)
The article with the title: Touchless palm print recognition system design using Gray Level Co-occurrence Matrix feature with K-Nearest Neighbor classification in MATLAB has been retracted at the request of the Editor-in-Chief. The retraction of this article is due to problems with the authenticity of the submitted article.